Effect of casein-whey ingredient blends on the protein stability of model infant formulas. (March 2023) - Mc Entee, Sinead A.; Murphy, Eoin G.; Lawless, Fergal N.; Kelly, Alan L.; McCarthy, Noel A.
Abstract: Milk protein concentrate (MPC 80), skim milk powder, acid whey protein concentrate (aWPC 35), cheese whey protein concentrate and isolate (cWPC 35 and cWPI) were assessed for suitability in infant formula (IF) applications with total solids similar to commercial ready-to-drink applications. Serum-phase compounds including phosphate, citrate and chloride in casein-rich streams, especially aWPC 35, played an important role in controlling whey protein thermal aggregation. Replacing cWPC 35 with cWPI improved protein stability at UHT temperatures, indicating that removal of minerals from whey protein streams could increase thermal stability of formulations. At HTST temperatures (95 °C), lactose appeared to have a protective effect against protein denaturation. At 140 °C, however, lactose contributed to cascading Maillard reactions triggering complete protein destabilisation; this occurred most rapidly in MPC 80 formulations that were comparatively low in serum-phase calcium-binding species (phosphate and citrate). These findings highlight how innate minerals and lactose impact protein stability during IF manufacture.